2021
DOI: 10.3390/ijms22136731
|View full text |Cite
|
Sign up to set email alerts
|

Plant RNA Binding Proteins as Critical Modulators in Drought, High Salinity, Heat, and Cold Stress Responses: An Updated Overview

Abstract: Plant abiotic stress responses are tightly regulated by different players at multiple levels. At transcriptional or post-transcriptional levels, several RNA binding proteins (RBPs) regulate stress response genes through RNA metabolism. They are increasingly recognized as critical modulators of a myriad of biological processes, including stress responses. Plant RBPs are heterogeneous with one or more conservative RNA motifs that constitute canonical/novel RNA binding domains (RBDs), which can bind to target RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 122 publications
0
19
0
Order By: Relevance
“…The cspB gene, which encodes the cold shock protein B, was introduced into maize to give drought tolerance [129]. The cspB transgenic plant retains RNA stability and translation during drought stress, maintaining normal cellular function [152,153]. More profound knowledge of interactions between growth-promoting microbes and plants is another promising approach to the abiotic stress problem in many plants (PGPM) [132,154].…”
Section: Improvement Of Drought Tolerance Using Molecular Toolsmentioning
confidence: 99%
“…The cspB gene, which encodes the cold shock protein B, was introduced into maize to give drought tolerance [129]. The cspB transgenic plant retains RNA stability and translation during drought stress, maintaining normal cellular function [152,153]. More profound knowledge of interactions between growth-promoting microbes and plants is another promising approach to the abiotic stress problem in many plants (PGPM) [132,154].…”
Section: Improvement Of Drought Tolerance Using Molecular Toolsmentioning
confidence: 99%
“…The functional annotation revealed that the candidate gene for DFW, Phvul . 002G122100 on chromosome Pv02 encodes an RNA-recognition motif protein, which plays a comprehensive biological function (critical modulators) in abiotic stress (drought, heat flooding, cold and high salinity) responding processes in plants [106]. Zhou et al [107] observed that the RNA-recognition motif gene “OsCBP20” from rice confers abiotic stress tolerance in escherichia coli .…”
Section: Discussionmentioning
confidence: 99%
“…In plants, several studies have been conducted for the transcriptome-wide identification of coding RBPs by employing the RIC method [ 22 , 49 , 59 , 65 , 66 ], which identifies the RBPs linked to polyadenylated poly(A) RNAs. Several efficient RBPs identification methods have been developed which are available to isolate the genomewide RBPs in plants, including XRNAX [ 51 ], CARIC [ 13 ], and PTex ( Figure 4 ) [ 67 ].…”
Section: Transcriptome-wide Identification Of Rbpsmentioning
confidence: 99%